Development of Triton Bay Tourism Object in Lobo Village, Kaimana Regency, West Papua Province - Aboda, Monika; Lasaiba, Mohammad Amin; Manakane, Susan Evelin (Jurnal Pendidikan Geografi Unpatti, 2023)
Tourism organizations are essential for advancing development in our country, especially within regions. This research aims to examine the development of tourism in Teluk Triton, located in the Kaimana Regency of West Papua Province. The method employed in this study is the SWOT analysis method to identify the Strengths, Weaknesses, Opportunities, and Threats to optimize the development of Teluk Triton as a tourist destination in the Lobo Village of Kaimana Regency, West Papua Province. The research findings indicate that strategic measures are required to address weaknesses and capitalize on existing opportunities to optimize Teluk Triton's development as a tourist attraction. Enhancing infrastructure, improving accessibility, collaborating with private entities, online promotion, and an active role of the government in developing and conserving the tourist site will play a pivotal role in realizing the potential of Teluk Triton as an attractive and sustainable tourism destination.